Improved clinical outcome of lupus nephritis during the past decade: importance of early diagnosis and treatment. Issue 5 (1st May 2003) - Fiehn, C; Hajjar, Y; Mueller, K; Waldherr, R; Ho, A D; Andrassy, K
Abstract : Objective: To evaluate the differences in the outcome of lupus nephritis diagnosed either in the 1980s or the 1990s in Heidelberg, Germany. Methods: Fifteen patients with biopsy confirmed lupus nephritis (LN) were followed up between 1980 and 1989 and 41 patients were followed up between 1990 and 2000. Their status at diagnosis and their treatment schedules and outcome were analysed. 68% had WHO IV nephritis. Results: In the decade from 1990 to 2000 there was significantly less proteinuria (46 v 17 g/l, p=0.008), significantly lower rates of renal failure (40% v 17%, p=0.02), and fewer histological signs of chronicity (33% v 10%, p=0.01) at the time of diagnosis of LN than in the decade from 1980 to 1989. The mean (SD) time from the first appearance of proteinuria until kidney biopsy was significantly shorter in the later decade (15.4 (15.6) v 3.9 (4.7) months). Although treatment schedules were not significantly different, the outcome of the disease was significantly better in the patients who were diagnosed with LN between 1990 and 2000 (p=0.045). Whereas 6/15 (40%) patients between 1980 and 1989 had terminal renal failure after a mean time of 94 months, in the group of 1990–2000 no patient developed terminal renal failure (median observation time 24 months). In both groups one patient died from infection. A high chronicity index in histology and the presence of arterial hypertension or renal failure, or both, at the time of diagnosis were significant risk factors for the development of terminal renal failure in the course of the disease. Conclusions: The outcome of patients with newly diagnosed LN was significantly better between 1990 and 2000 than between 1980 and 1989. Kidney damage and chronic histological changes at time of diagnosis were significantly less common between 1990 and 2000, which is attributable to earlier diagnosis and treatment in the later decade.